Anatomical classification of the segmental arterial branches on the renal artery in pig kidneys - Pendovski Lazo; Ilieski Vlatko; Petkov Vladimir; Popovska-Percinic Florina (Macedonian Veterinary Review, 2009)
The aim of this article is to present a classification of pig kidneys segmental arterial system based of the distribution on the segmental arteries inside the renal parenchyma. A total of 109 pig kidneys taken form two adult breeds (62 kidneys form hybrid breed landrace/yorkshire and 47 kidneys form hybrid breed dalland) slaughtered at age of 5 months and weignining of 95 kg (mean) were investigated. The anatomy of arterial vessels was studied on three-dimensional silicone S10 corrosion casts prepared together with the kidney collecting system. There was one artery per kidney in all investigated specimens that primary branched into two arteries, one cranial and the one caudal branch in a 93.54% in a hybrid breed landrace/yorkshire and in the 89.36% hybrid breed dallnad. In the rest of 6.46% hybrid breed landrace/yorkshire and 10.64% hybrid breed dallnad the renal artery was branched into one dorsal and one ventral primary branch.(p>0.05) According the way of witch the secondary segmental arteries were branching, the regions of their visualization as well their position inside the renal parenchyma, three different arterial systems were classified as: type I(79.03% landrace/yorkshire vs. 82.97% dallnad ) witch was wery variable and can be found in three subtypes(Ia, b, c), type II (14.51% landrace/yorkshire vs. 6.39% dallnad) and type III(6.46% landrace/yorkshire vs. 10.64% dallnad) (p>0.05). According the results, the vascular positions of segmental arteries in pig kidneys allow blood supply inside in kidneys to be divided into separate regions witch is necessary condition for segmental resection of kidneys during vascular partial nefroctomy as well for their use in clinical experimental medicine.